ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN PROPERTI YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2012-2014: Property Company, Liquidity Ratios, Solvency Ratios, Profitability Ratios, Activity Ratios. - lailatul maulidiyah; Henny Dwijayani (eBA Journal: Journal Economic, Bussines dan Accounting, 2017)
Financial aspect is the aspect most widely used by financial analysts. Thisaspect is used on the assumption that, in addition to the condition of thecompany's financial situation may reflect the actual state of the company, thecompany's financial condition also show whether the business carried on thecompany profitable / no. The purpose of this study was to determine the financialperformance of property companies listed on the Indonesia Stock Exchange in2012-2014, by comparing the results of the financial performance of eachcompany the property using the formulas for the financial ratios liquidity ratios,solvency ratios, profitability ratios and activity ratios.From the analysis it can be seen on the company's financial performancethat the property of their respective annual financial ratios of property companieshas increased and decreased in accordance with the financial level that occur ineach property companies every year.